Clinical handover practice in the emergency and trauma department of SASMEC@IIUM: an observational qualitative study - Ahayalimudin, Nurul'Ain; Mohd Noh, Hairanni; Mohd. Shah, Aida Nur Sharini; Norazman, Nur Zaharatul Zahirah (IIUM Press, 2023)
Introduction: Where there is a high patient turnover rate and a fast-paced atmosphere with unpredictable events, such as in the emergency and trauma department (ETD), the likelihood of miscommunication and errors rises. Communication between the shifts or among the employees must be informed of crucial information to ensure safety and effective clinical handover practices. Therefore, the primary goal of this study is to discover clinical handover practices that can improve communication between emergency healthcare personnel (HCPs) and within various departments. Objective: To identify the existing shift handover procedures, the resources and supports available to improve clinical handover efficacy, as well as the factors that promote and impede clinical handover effectiveness among the emergency staff. Methods: This descriptive, qualitative study used a purposive sampling strategy, obtaining 33 nurses, doctors, and assistant medical officers (AMOs) where the data reached saturation. Open-ended questions using a topic guide interview were used to elicit the participants’ opinions on the current clinical handover procedures in the department. Thematic analysis was used to analyse the data after the sub-themes and themes were created. Results: Six themes were identified for this study, consisting of 1) learning methods of clinical handover, 2) information passed to the next shift, 3) information expected to be received, 4) opinions on current handover, 5) handover effectiveness, and 6) suggestions for improvement. Conclusion: The emergency HCPs have diverse backgrounds in clinical handover and working experiences due to having previously worked in other hospitals or departments. In this study, they discussed their own experiences with clinical handover in the department as well as the variables that determine how well the clinical handover process works. The findings were focused on the components that the participants believed may be advantageous for the general improvement of the clinical handover.